PENDAPATAN PEDAGANG PADA MASA PANDEMI COVID- 19 DI PASAR TANAWANGKO DESA BORGO KABUPATEN MINAHASA - Rivaldy Angelo Karundeng; Gene Henfried Meyer Kapantow; Theodora M. Katiandagho (AGRI-SOSIOEKONOMI, 2021)
This study aims to determine the income of horticultural traders in Tanawangko Market, Borgo Village, Tombariri District, Minahasa Regency during the Covid-19 pandemic. This research was conducted for two months, namely in October and November 2020. The method used in this study was a survey method by taking primary data and secondary data. The data analysis used in this research is descriptive analysis which is presented in tabular form. The results of research, total revenue of Rp. 2,909,750 while the total cost of Rp. 2,097,450 consisting of business capital and market retribution costs. The profit of Tanawangko market traders during the Covid 19 pandemic was an average of IDR 812,300 / week.